2000
DOI: 10.1111/j.1541-1338.2000.tb00915.x
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of State Enterprise Zone Policies

Abstract: Our analysis looks at the impact of state enterprise zones in six states (California, Florida, New Jersey, New York, Pennsylvania, and Virginia) on housing values, occupancy rates, and economic well-being of zone residents. Zones did not lead to increased housing prices or occupancy rates, nor did they positively impact income and employment. Copyright 2000 by The Policy Studies Organization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 4 publications
4
39
0
Order By: Relevance
“…There are at least four reasons why the program effects in Table 2 appear so much larger than those in Greenbaum and Engberg (2000) and other appraisals of state enterprise zone programs.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…There are at least four reasons why the program effects in Table 2 appear so much larger than those in Greenbaum and Engberg (2000) and other appraisals of state enterprise zone programs.…”
Section: Resultsmentioning
confidence: 92%
“…In the context of state programs, Greenbaum and Engberg (2000) use propensity scores to select a comparable sample of zip codes for comparison of the effects of targeted incentives and compare the effects of actual zone selection versus zip code characteristics. They find that on average, enterprise zones became worse, relative to non-zones, over the 1980's, but that once you control for area characteristics, the effects of being in a zone were mostly insignificant.…”
mentioning
confidence: 99%
“…Therefore there is not a good sample of employment prior to designation for the majority of enterprise zones. To find an appropriate control group, this study expands on Dardia's [9] model and draws on the procedure used by Greenbaum and Engberg [13,14] by using a propensity score matching model. The propensity score is the conditional probability that any census tract is designated as an enterprise zone, given the observed demographic characteristics of the tract in 1990, and the employment characteristics in 1992.…”
Section: Study Design and Methodologymentioning
confidence: 99%
“…Examining urban enterprise zones in three states, Engberg and Greenbaum (1999b) found that zones did have some positive effects on home ownership and occupancy rate, but that the zones also had some negative effects on labor market outcomes. Greenbaum and Engberg (2000) found that zones have, at best, no effect on housing market, income, or employment outcomes in the urban areas of six states. Bondonio and Engberg (2000) found that zones have no effect on employment outcomes in five states, even when the monetary generosity of the incentives was taken into account.…”
Section: Introductionmentioning
confidence: 95%
“…To estimate the average ZIP employment, the size class averages are multiplied by the number of establishments in each size class in each ZIP and summed over the size classes. Although this unofficial ZIP code tabulation has not been subjected to the Census Bureau's high-quality control checks, it has proven to be very informative in previous research (Bondonio and Engberg, 2000;Greenbaum and Engberg, 2000).…”
Section: Business Datamentioning
confidence: 99%